If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1y = -6 Solving 6 + -1y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1y = -6 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = -6 + -6 -1y = -6 + -6 Combine like terms: -6 + -6 = -12 -1y = -12 Divide each side by '-1'. y = 12 Simplifying y = 12
| 4/3*3.14(7.75)^3 | | 253-5x=40x+17 | | 15-9x=2x-7 | | 3x^2-5x+2y-4=0 | | 3y/6 | | (-5)-(-8)-4y+(-4x)-(-7y)-(-10x)= | | 77+5(x+9)=x | | 9x-(-7y)-(-6)+9-(-2x)-4y= | | (-x)-(-6)+(-4x)+(-7y)-1-8y= | | (-8)+(-8x)+(-y)+4+(-x)+(-9y)= | | -4a^3*2b^2= | | (-8y)-1+y+(-x)-3x-(-8)= | | 10x^24=56 | | 6x-293=6x-13 | | 3y+4+6x-3x-2y-2= | | 10y-6x+4-4x+6y-6= | | 5y-2y+5x+4x-7+9= | | b*c*d*c= | | 3y-1-2y-2x+8-4x= | | a*b*-3*-3= | | 64-6x=8-10x | | p*6*q*-1= | | -3*n*2*m= | | -2*4*m*m= | | y=x^2+(m-1)x+4 | | c*c*3*b= | | 4*a*b*4= | | m*2*n*3= | | c*c*c= | | b+4/4-b-10/2 | | b*b*a= | | 48x^2-8x^3=0 |